Issues with interpreting the social and legal value of a person in the context of the integrative type of legal-awareness - Shevchenko, Anatolii Yevheniiovych; Kudin, Serhii Volodymyrovych; Kamarali, Svitlana Yevheniivna; Dei, Maryna O. (Accent Graphics Communications, 2020)
The study of the essence of the social and legal value of a person within the framework of modern concepts of legal awareness will be incomplete, if limited only to natural and normative approaches to the definition of the concept of “law”. Being a multifaceted, multifunctional social phenomenon, law manifests itself in various forms, which requires setting our efforts to understanding the social and legal value of a person in the context of integrative legal awareness. Given the ambiguity of the attitude of scientists to the integrative concept of legal-awareness, there are appropriate difficulties in identifying clear conceptual positions, on the basis of which it is possible to integrate existing positive aspects of certain approaches to the definition of the concept of “law”, in our opinion, it is still necessary to continue to carry out scientific developments in this direction, which is conditioned by the needs of society, enhancing the role of a person as a creator of the historical process.

Вивчення сутності соціально-правової цінності, а людина в рамках сучасних концепцій легальної свідомості буде неповною, якщо обмежитися лише природними і нормативні підходи до визначення поняття “Закон”. Будучи багатогранним, багатофункціональним соціальним явищем, право проявляється у різних формах, які вимагає налаштування наших зусиль на розуміння соціальних і юридична цінностях особи в контексті інтегративної легальної обізнаності. Враховуючи неоднозначність ставлення вчених до інтегративні концепції правосвідомості існують відповідні труднощі у визначенні чіткого концептуального позиції, на основі яких можна інтегрувати існуючі позитивні аспекти певних підходів до визначення поняття "закон", на наш погляд, необхідно продовжувати здійснювати наукові розробки в Росії за цим напрямком, який зумовлений потребами суспільства, посилення ролі людини як творця історичного процесу.
Keywords: law; law; social value; legal value; integrative awareness; socio-legal value; закон; право; соціальна цінність; юридична цінність; інтегративна обізнаності; соціально-правової цінності